Uji Validitas dan Reliabilitas Kondisi Fisik pada Atlet Tunanetra Total Pelatda Jabar 2023 - Gempar Al-Hadist; Martin Martin; Arif Fajar Prasetiyo (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This research aims to fulfill one of the many research proposals for health and recreation physical education and also aims to determine the results of tests for the validity and reliability of physical conditions in athletes with total visual impairment at the 2023 JABAR Pelatda. The approach used in this research is a qualitative approach. In this research, the author used a total sampling technique, namely the entire population of 8 people. The results of this study can be concluded that the validity of the flexibility test (sit and reach) has a high interpretation. And the reliability is high because the reliability value is above 15 so it can be said to be high reliability